Legislative bargaining and the dynamics of public investment - Marco Battaglini; Salvatore Nunnari; Thomas Palfrey (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2011)
We present a legislative bargaining model of the provision of a durable public good over an infinite horizion. In each period, there is a societal endowment which can either be invested in the public good or consumed. We characterize the optimal public policy, defined by the time path of investment and consumption. In each period, a legislature with presentatives of each of n districts bargain over the current period's endowment for investment in the public good and transfers to each district. We analyze the Markov perfect equilibrium under different voting q-rules where q is the number of yes votes required for passage. We show that the efficiency of the public policy is increasing in q because higher q leads to higher investment in the public good and less pork. We examine the theoretical equilibrium predictions by conducting a laboratory experiment with fiveperson committees that compares three alternative voting rules: unanimity (q=5); majority (q=3); and dictatorship (q=1).
Keywords: D71; D72; C78; C92; H41; H54; 330; dynamic political economy; voting; public goods; bargaining; experiments